(3cJGH ajeG jdRe ef Yde GdbQGAI hYde GdQSes
(3ChdgG (B:s
(3GdMeO ddg JYGdi GdLHGQ GdSJGQ GdYRjR CeG HYO abO SCdfi Yf CUMGH ENhGfi Cf CLeY CYTGQ BjGJ GdbQBf aLeYJgG s
(3BNQgG (B:s
(3LedI YOO GdCYTGQ Ydi GdhaGb SJeGFI YTQ hYTQI YTQkG hSJ BjGJ eY aGJMI GdcJGH JeJ JeGe ChdOi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdbQGAGJ hGdJLhjOs